Seismic Anisotropy Analysis Beneath Sumatra Revealed by Shear-Wave Splitting - Arya Dwi Candra; Bagus Jaya Santosa; Gazali Rachman (Geological Agency, 2017)
DOI: 10.17014/ijog.4.3.169-179A shear-wave splitting analysis was determined to observe anisotropic structures of an upper mantle layer beneath Sumatra. The data were collected from 35 BMKG stations with the magnitude of more than 6.25 Mw and the epicentre of 85o - 140o. A shear-wave splitting measurement was calculated by using Splitlab based on three methods simultaneously. The result of the shear-wave splitting measurement in the Sumatra Forearc and Fault Zone shows that there are two anisotropic layers. The first layer has a dominant-fast-polarization direction that is parallel with a trench, and has the delay time duration of 0.5 - 0.9 s-. It is presumed that it is caused by a shear-strain as a result of the existences of Mentawai and Sumatra Fault Zones. The second layer has a dominant-fast-polarization direction that is perpendicular to the trench with the delay time duration of about 1.1 - 1.9 s-. It is presumed that it is caused by a movement of a subduction plate on a mantle wedge. The measurement in the backarc shows that there is only one anisotropic layer that is a subduction plate. It is also found that there is a transition of an orientation change on the subduction plate between Sumatra and Java. The change of the polarization direction is probably related to the age difference and the direction velocity of the absolute plate movement (APM) from Sumatra to Java.